Comparative study of six SARS-CoV-2 serology assays: Diagnostic performance and antibody dynamics in a cohort of hospitalized patients for moderate to critical COVID-19. (12th January 2022) - Chamkhi, Sameh; Dhaouadi, Tarak; Sfar, Imen; Mokni, Salma; Jebri, Alia; Mansouri, Dhouha; Ghedira, Salma; Ben Jemia, Emna; Ben Boujemaa, Samia; Houissa, Mohamed; Aouina, Hichem; Ben Abdallah, Taïeb; et al.
Background: To overcome the COVID-19 pandemic, serology assays are needed to identify past and ongoing infections. In this context, we evaluated the diagnostic performance of 6 immunoassays on samples from hospitalized patients for moderate to critical COVID-19. Methods: 701 serum samples obtained from 443 COVID-19 patients (G1: 356 positive RT-PCR patients and G2: 87 negative RT-PCR cases) and 108 pre-pandemic sera from blood donors were tested with 6 commercial immunoassays: (1) Elecsys Anti-SARS-CoV-2, Roche (Nucleocapsid, N), (2) Elecsys Anti-SARS-CoV-2 S, Roche (Spike, S), (3) Vidas SARS-COV-2 IgM/IgG, BioMérieux (S), (4) SARS-CoV-2 IgG, Abbott (N), (5) Access SARS-CoV-2 IgG, Beckman Coulter (Receptor Binding Domain), and (6) Standard F COVID-19 IgM/IgG Combo FIA, SD Biosensor (N). Results: Global sensitivities of the evaluated assays were as follows: (1) Roche anti-N = 74.5% [69.6–79.3], (2) Roche anti-S = 92.7% [84.7–100], (3) Vidas IgM = 74.9% [68.6–81.2], (4) Vidas IgG = 73.9% [67.6–80.1], (5) Abbott = 78.6% [63.4–93.8], (6) Beckman Coulter = 74.5% [62–86.9], (7) SD Biosensor IgM = 73.1% [61–85.1], and (8) SD Biosensor IgG = 76.9% [65.4–88.4]. Sensitivities increased gradually from week 1 to week 3 as follow: (1) Roche anti-N: 63.3%, 81% and 82.1%; (2) Vidas IgM: 68.2%, 83.2% and 85.9%; and (3) Vidas IgG: 66.7%, 79.1% and 86.6%. All immunoassays showed a specificity of 100%. Seropositivity was significantly associated with a higher frequency of critical COVID-19 (50.8% vs. 38.2%), p = 0.018, OR [95% CI] = 1.668 [1.09–2.553]. Inversely, death occurred more frequently in seronegative patients (28.7% vs. 13.6%), p =3.02 E-4, OR [95% CI] = 0.392 [0.233–0.658]. Conclusion: Evaluated serology assays exhibited good sensitivities and excellent specificities. Sensitivities increased gradually after symptoms onset. Even if seropositivity is more frequent in patients with critical COVID-19, it may predict a recovery outcome.